AN ESTIMATION OF CHINESE RENMINBI EXCHANGE RATE IMPACT ON THE REAL EXPORTS OF INDONESIA TO THE US: IS THERE A J-CURVE? - Putriani, Diyah (Journal of Indonesian Applied Economics, 2016)
This paper seeks whether a J-Curve exists on the impact of changes in the Chinese Renminbi (RMB) exchange rates on bilateral exports of Indonesia to the United States (US), particularly in the long run. The Johansen cointegration procedures and Vector Error Correction Model (VECM) regression are applied. The cointegration test shows that there are long-term relationships amongst real GDP of US, Indonesian Rupiah (IDR), real exchange rates and volatility, and Chinese RMB real exchange rates. The result shows that the RMB exchange rate has a negative significant impact (substitution relationship) on Indonesian export to the US. The result also suggests a dissatisfaction of the Marshall-Lerner condition indicating the J-curve phenomenon does not exist.